2013
DOI: 10.17503/agrivita-2013-35-3-p296-303
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE OF EGGPLANT (Solanum melongena L.) TO COMBINATION OF INORGANIC-ORGANIC N AND EM4

Abstract: A research to reduce application of N inorganic fertilizer through combination of inorganic-organic N and EM4 on eggplant has done on paddy field in Poncokusumo, Malang Regency, East Java, from June to September 2013. The experiment used a randomized complete block design with two factors and three replications. The first factor was the combination of inorganic-organic N fertilizer, ie. 100% urea, 75% urea + 25% goat manure, 50% urea + 50% goat manure, and 25% urea + 75% goat manure . The second factor was dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…These current findings suggested that the combination of organic and inorganic fertilizers could potentially be beneficial to increase yield and nutritional quality in fruit of eggplant. Maghfoer, Soelistyono, & Herlina, 2013; also found that, at the same nitrogen application rate, mixing organic (goat manure) and inorganic nitrogen (urea) produced higher yield in eggplant than those fertilized solely with inorganic nitrogen. The application of organic fertilizer was not only as source of multiple elements but also improved hydraulic properties of soil or growing substrate, i.e.…”
Section: Inorganic Npk For Complementing Soil-manure Mixed Substratementioning
confidence: 82%
“…These current findings suggested that the combination of organic and inorganic fertilizers could potentially be beneficial to increase yield and nutritional quality in fruit of eggplant. Maghfoer, Soelistyono, & Herlina, 2013; also found that, at the same nitrogen application rate, mixing organic (goat manure) and inorganic nitrogen (urea) produced higher yield in eggplant than those fertilized solely with inorganic nitrogen. The application of organic fertilizer was not only as source of multiple elements but also improved hydraulic properties of soil or growing substrate, i.e.…”
Section: Inorganic Npk For Complementing Soil-manure Mixed Substratementioning
confidence: 82%
“…Perlakuan pukan ayam+BP (T9) memiliki kandungan hara N dan P relatif lebih tinggi dibanding pupuk lainnya, hal ini menyebabkan proses pembentukan daun lebih cepat. Ketersediannya N dan P yang cukup meningkatkan pertumbuhan organ-organ tanaman, salah satunya proses pembentukan daun (Maghfoer et al, 2013).…”
Section: Pertumbuhan Tanaman Okraunclassified
“…According to Syafruddin and Safrizal (2013), the application of EM4 by concentration of 15 mL/L with application interval once in 2 weeks could increase fruit weight of red chili. Moreover, Maghfoer et al (2013) stated that the application of EM4 by dose of 30 L/ha would produce the highest yield of eggplants.…”
Section: Journal Of Degraded and Mining Lands Management 540mentioning
confidence: 99%
“…Maghfoer et al (2013) reported that combination of urea 75% and goat manure 25% reduced the application of urea and produced the best yield of eggplants for about 48.70 t/ha. According to Adil et al (2006), the application of organic fertilizer could improve soil fertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation